EP400NL is involved in PD-L1 gene activation by forming a transcriptional coactivator complex - Li Z; Kim H; Kim J; Park JH (Elsevier B V, 2023)
EP400 is an ATP-dependent chromatin remodelling enzyme that regulates DNA double-strand break repair and transcription, including cMyc-dependent gene expression. We previously showed that the N-terminal domain of EP400 increases the efficacy of chemotherapeutic drugs against cancer cells. As the EP400 N-terminal-Like (EP400NL) gene resides next to the EP400 gene locus, this prompted us to investigate whether EP400NL plays a similar role in transcriptional regulation to the full-length EP400 protein. We found that EP400NL forms a human NuA4-like chromatin remodelling complex that lacks both the TIP60 histone acetyltransferase and EP400 ATPase. However, this EP400NL complex displays H2A.Z deposition activity on a chromatin template comparable to the human NuA4 complex, suggesting another associated ATPase such as BRG1 or RuvBL1/RuvBL2 catalyses the reaction. We demonstrated that the transcriptional coactivator function of EP400NL is required for serum and IFNγ-induced PD-L1 gene activation. Furthermore, transcriptome analysis indicates that EP400NL contributes to cMyc-responsive mitochondrial biogenesis. Taken together, our studies show that EP400NL plays a role as a transcription coactivator of PD-L1 gene regulation and provides a potential target to modulate cMyc functions in cancer therapy.
Keywords: Cancer; Chromatin remodelling; Epigenetic; H2A.Z; PD-L1; cMyc; Humans; Adenosine Triphosphatases; ATPases Associated with Diverse Cellular Activities; B7-H1 Antigen; Carrier Proteins; DNA Helicases; Histones; Transcription Factors; Transcriptional Activation